Observations on the reproduction and life cycle of Plusiotis costata Blanchard, 1851 (Coleoptera: Melolonthidae: Rutelinae). - Morón, Miguel Ángel (Instituto de Ecología, A.C., 2010)
The reproductive system of Plusiotis costata Blanchard is described. The male system consist of two testes, each testis with six follicles, two vasa deferentia, two accessory glands, ejaculatory bulb, ejaculatory duct, and complex aedeagus. The female system is formed by two ovaries, each with six ovarioles and two lateral oviducts, the common oviduct, bursa copulatrix, spermatheca with its gland, and genital chamber with four pairs of genital plates. Information on copulation behavior and biannual life cycle of P. costata in captivity is also included.